Education for Employment: Is the Null Hypothesis Proven Too Frequently? - Hollingsworth, Mary Ann (European Scientific Journal, ESJ, 2017)
Employment prospects vary for college graduates, with a few courses of study leading to an overabundance of opportunity. For the majority of students, there is significant mismatch between training preparation and actual job demand in either type of job, location of job, or skills required in job. This qualitative study examined integration of desired employment activities and aptitudes into 30 sections of different graduate courses in counseling over four school years to ascertain student perception of enhancement of job preparation. Activites focused on four areas that research indicated to offer benefit for student employment preparation: engagement in work-simulated skills practice; engagement in course group activiteis; participation in service learning volunteerism; and student pro-activity. Many students were already working in the general field of study such as school teachers pursuing a degree in school counseling. Student feedback indicated perceived benefit and efficacy toward preparation for desired post-degree job. Further study is indicated in this potential integration with expansion of study into multiple fields of study and into both undergraduate and graduate programs.